Sodium butyrate supplementation improves growth performance, gut health, hepatic enzyme activities, and disease resistance against Aeromonas hydrophila in Labeo rohita - Aafaq Younas; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Wazir Ali; Ayesha Khizar; Ayesha Tanveer; Sadaf Khadim (Veterinary Research Communications, 2026)

Effects of dietary sodium diformate in improving growth performance, nutrient digestibility, physiological responses, and survival against multiple stressors in Labeo rohita under high stocking density - Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Wazir Ali; Ayesha Khizar; Rahila Kausar; Nayyab Attiq; Anam Ilyas (Aquaculture International, 2026)

Structural and physiological adaptations conferring herbivory resistance in wild olive (Olea europaea L. subsp. cuspidata) - Faakeha Islam; Syed Mohsan Raza Shah; Farooq Ahmad; Mansoor Hameed; Sana Basharat; Sana Fatima; Ansar Mehmood; Zahida Parveen; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Khawaja Shafique Ahmad (Physiology and Molecular Biology of Plants, 2026)

MOF-based composite catalysts for CO2 reduction: Recent advances and perspectives - Asad Ur Rehman; Syed Shoaib Ahmad Shah; Sami Ullah; Arooj Fatima; Ibrahim A. Shaaban; Muhammad Sufyan Javed; Awais Ahmad; Muhammad Altaf Nazir (Environmental Research, 2026)

Treatment outcomes of hydrocephalus management strategies in patients with cerebellopontine angle lesions - Shah Khalid; Rabeet Tariq; Salaar Ahmed; Fatima Zahra; Altaf Ali Laghari; Syed Ather Enam (Acta Neurologica Belgica, 2026)

Dietary sodium propionate enhances growth performance, digestive enzymes, haematology and immunity in Wallago attu - Ayesha Tanveer; Noor Khan; Mahroze Fatima; Hafiz Abdullah Shakir; Ayesha Khizar; Syed Zakir Hussain Shah; Laiba Kareem; Saba Aftab; Malik Muhammad Ramzan; Ahmed Mustafa; Simon John Davies (Journal of Fish Biology, 2026)
Sodium propionate (SP), a short‐chain fatty acid, has been widely used as a feed additive to improve fish growth and health status. The current experiment was designed to investigate the effects of dietary SP on growth, enzymatic activities, haematology and immune status of Wallago attu . Fingerlings (initial weight = 8.80 ± 0.58 g) were fed with graded levels of SP comprising 0.0, 0.5, 1.0, 2.0, 4.0 and 8.0 g/kg levels for 60 days in triplicate glass aquaria (89 × 58 × 61 cm [length × width × depth]). The results showed significant ( p W. attu fingerlings when fed with graded levels of SP. In conclusion, the SP supplementation in W. attu showed best results ranged between 2 and 4 g/kg level by improving fish health and growth performance.

Zingiber officinale as a Functional Aquafeed Additive: Effect on Growth, Immunity and Oxidative Status in Fish and Shrimp - Rukhma Asif; Syed Zakir Hussain Shah; Mahroze Fatima (Aquaculture International, 2026)

Phyto-synthesis and pharmacological evaluation of AgNPs using hydroponic coriander for MRSA infected wounds - Syed Damin Abbas Hamdani; Hunaiza Fatima; Mahnoor Ilyas; Alvina Gul; Faiq Musharaf Sabih; Mustafeez Mujtaba Babar (Advances in Traditional Medicine, 2026)

A comprehensive review on thermo-responsive targeted and functional therapy for management of rheumatoid arthritis - Huma Hameed; Syed Sharf ud Din; Muhammad Zaman; Muhammad Ahsan Waqar; Kainat Fatima; Abdullah Ashraf; Huzaifa Malik; Ahmad Salawi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retraction Note: Mitigating potentials of natural herbal supplements against heavy metal toxicity in freshwater fish, Cyprinus carpio - Arzoo Fatima; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K. Sarker; Khalid A. Al-Ghanim; Eman Naeem (Aquaculture International, 2026)

Dietary Hydrilla verticillata extract enhances growth and immune defense against Aeromonas hydrophila in Labeo rohita - Faiza Khanam; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Wazir Ali; Sadaf Khadim; Sobia Nisa; Mehwish Khan (Veterinary Research Communications, 2026)

Formulation Design of Glucuronoxylan-Based Stimuli-Responsive Microparticles for Zero-Order Drug Delivery - Saleha Babar; Fatima Akbar Sheikh; Syed Nasir Abbas Bukhari; Muhammad Tahir Haseeb; Arshad Ali; Nisar Ul Khaliq; Ranya Abdulrahman Alafar; Mohamed Abdelwahab Abdelgawad; Ameeduzzafar Zafar; Naveed Ahmad (Journal of Pharmaceutical Innovation, 2026)

Vitamin D supplementation and its role in modulating ovarian reserve and oxidative stress in infertile females - Arfa Azhar; Syed Mahboob Alam; Faiza Alam; Fatima Abid; Aysha Habib; Rehana Rehman (PharmaNutrition, 2026)

Climate-driven Modifications in Structural and Functional Traits of Couch Grass [Cynodon Dactylon (L.) Pers.] along Elevation Gradient - Sana Fatima; Farooq Ahmad; Zahida Parveen; Sana Basharat; Mansoor Hameed; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Syed Mohsan Raza Shah; Raza Shah; Muhammad Ashraf; Muhammad Kaleem; et al. (Journal of Soil Science and Plant Nutrition, 2026)

Trait dynamics of endemic Festuca species reveal cold-resilience across elevation gradient - Khawaja Shafique Ahmad; Syed Mohsan Raza Shah; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Ummar Iqbal; Ansar Mehmood; Sana Fatima; Wisal Muhammad Khan; Muhammad Ashraf; Hazem M. Kalaji; Manzer H. Siddiqui (Acta Physiologiae Plantarum, 2026)

Discovery and structural elucidation of novel antioxidant Scoparioate A from Artemisia scoparia using spectroscopic analysis and DFT computational techniques - Irshad Yasmin; Ehab A. Abdelrahman; Bushra; Dilfaraz Khan; Khalil ur Rehman; Fatima Syed; Shafiullah Khan; Noura Al-Dayan; Sameerah I. Al-Saeedi; Mohammed Ali A. Majrashi (Natural Product Research, 2026)

Meta-analysis of Moringa oleifera supplementation as functional feed additive and nutritional feed ingredient: effects on growth performance, hematological indices, and liver enzyme activities in fish and shrimp - Isha Imtiaz; Syed Zakir Hussain Shah; Mahroze Fatima (Aquaculture International, 2026)

Manganese supplementation in aquafeed: Current knowledge, research gaps, and future prospects for growth and health optimization - Rubina Hayat; Syed Zakir Hussain Shah; Mahroze Fatima; Wazir Ali; Areej Farooq (Journal of Trace Elements in Medicine and Biology, 2026)

Root microstructural traits regulate ion homeostasis in bush morning glory (Ipomoea carnea Jacq.) for invasiveness success in saline environments - Syed Mohsan Raza Shah; Naila Hadayat; Jazab Shafqat; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Maham Zia; Zaheer Abbas; Zahida Parveen; Muhammad Ashraf; Ummar Iqbal; Ansa Asghar; et al. (The Science of Nature, 2026)

Implementing QbD for Nano-Pharmaceuticals and Complex Formulations to Achieve Predictable and High-Quality Outcomes - Rohan Panwar; Anuradha Mishra; Abhisar Sahu; Syed Naved Quadri; M. Z. Abdin; Saman Fatima (AAPS PharmSciTech, 2026)

Investigating the pesticidal efficacy of actinobacteria species against Sitophilus oryzae and Tribolium confusum - Syed Khalida Izhar; Shareen Fatima Rizvi; Anmol Gupta; Ahmed Alafnan; Saba Siddiqui; Uzma Shahab; Irfan Ahmad; Saheem Ahmad; Uzma Afaq (Journal of Stored Products Research, 2026)

Seed Priming with Osmolytes Ameliorates Salinity Tolerance in Maize (Zea mays L.) Through Embryonic Modifications - Paris Riaz; Ansa Asghar; Sana Fatima; Sana Basharat; Zahida Parveen; Mansoor Hameed; Farooq Ahmad; M. Sajid Aqeel Ahmad; Muhammad Ashraf; Faakeha Islam; Syed Mohsan Raza Shah; Qasim Ali (Journal of Plant Growth Regulation, 2026)

Ecological resilience of Gallon's curse (Cenchrus biflorus Roxb.) in hyperarid and hypersaline environments - Sana Basharat; Farooq Ahmad; Mansoor Hameed; Zahida Parveen; Muhammad Sajid Aqeel Ahmad; Muhammad Waseem; Ansa Asghar; Sana Fatima; Liu Pingwu; Mehwish Noor; Syed Mohsan Raza Shah; Muhammad Ashraf (Journal of Arid Environments, 2025)

Exome sequencing in a Pakistani male infertility cohort: perspective on molecular diagnosis, genetic heterogeneity, and diagnostic yield - Dapeng Zhou; Ambrin Fatima; Afrasiab Ahmed; Tehseen Ullah Khan Afridi; Haq Nawaz Khan; Mussarat Ashraf; Muhammad Naeem; Syed Babar Jamal; Ishtiaq Hassan; Erica E. Davis; Feng Zhang; Rehana Rehman; et al. (Molecular Genetics and Genomics, 2025)

Bioinformatics and immunoinformatics approaches in the design of a multi-epitope vaccine targeting CTLA-4 for melanoma treatment - Fatima Noor; Samiah Shahid; Muskan Fatima; Syed Zeeshan Haider; Zafer Saad Al Shehri; Faez Falah Alshehri; Abdur Rehman (Molecular Diversity, 2025)

Green Synthesis of Mangifera Indica Mediated NiO and NiMn2O4 Nanomaterials for Electrocatalytic Water Splitting - Fatima Masood; Shabbir Hussain; Muhammad Arif; Shahzad Murtaza; Muhammad Imran; Muhammad Bilal Tahir; Khurram Shahzad Munawar; Hamad M. Alkahtani; Amer Alhaj Zen; Syed Adnan Ali Shah (International Journal of Environmental Research, 2025)

Regulation of macrophage transcriptional dynamics during acute and chronic wound repair - Sk Rameej Raja; Mobbassar Hassan Sk; Syed Wajeed; Rigzin Yangdol; Ayushi Yadav; Himanshi Jindal; Arib Fatima; Arif Siddiquie; Laxmi Pulakat; Ramachandran Subramanian; Mirza S Baig (Inflammation Research, 2025)

Exploration of medicinal and nutritional value of Himalayan wild edible fruits: implications for sustainable health and functional foods - Syeda Khateeb Fatima; Rizwan Taj Khan; Munazza Nazir; Muhammad Manzoor; Syed Waseem Gillani; Mumna Munir; Muhammad Nasir; Wasim Akhtar; Shabir Ahmad; Manal Abdulaziz Binobead; M Ajmal Ali (Genetic Resources and Crop Evolution, 2025)

hMPV co-infections: Distinct immunopathogenic mechanisms and clinical implications of viral and bacterial pathogenesis - Syed Sib Tul Hassan Shah; Iqra Naeem; Nabeel Khalid Bhutta; Gao Han; Fatima Noor (Folia Microbiologica, 2025)

Genomic Insights into Poultry-Associated Staphylococcus Aureus from Haripur, Pakistan - Arif Ullah; Bushra Fatima; Mohammad Ejaz; Muhammad Ali Syed (Current Microbiology, 2025)

Magnetic MOF-Based Immunosensing Strategy with Quantum Dot Labeling for Efficient Electro-chemiluminescent Detection of Alpha-fetoprotein - Mariyam Fatima; Muhammad Faizan; Iqra Jabeen; Muhammad Fiaz; Ansar Ali; Syed Kashif Ali; Ali Bahadur; Shahid Iqbal; Sajid Mahmood; Ibrahim Jafri; Abd-ElAziem Farouk (Journal of Fluorescence, 2025)

Intrahepatic cholangiocarcinoma mortality in the USA, 1999–2020: a 21-year population-based analysis - Anoud Khan; Aryan Tareen; Syed Usama Ashraf; Imaan Shoaib Mufti; Maryam Karam; Fatima Ibrahim Ahmed; Syeda Neha Rasool; Rinad Akhtar; Ahrar Amin; Saqib Raza Khan (Cancer Causes & Control, 2025)

Modelling pandemic-induced spatially heterogeneous patterns in income shock, food insecurity and their driving factors: a case of Pakistan - Muhammad Sajjad; Syed Hassan Raza; Wajiha Haq; Syeda Fatima Rubab (Environment, Development and Sustainability, 2025)
While pandemic-related income shock (IS) compromises societal well-being by leading to food insecurity (FI) in developing countries, evaluating the spatial inequities of IS, FI, and their significant driving factors is imperative for informed and targeted interventions. In this context, we explore spatial disparities in IS and FI, model significant factors driving IS, and examine the potential association between FI and IS in Pakistan—a nation with ~ 255 million people and vulnerable to food crises—using Covid-19 as a case study. Through the integrated deployment of spatial, econometric, and statistical models, priority intervention areas for IS and FI are identified, enabling efficient resource allocation and informed decision-making. Furthermore, spatial relationships among IS, FI, and significant factors are visualized using bivariate mapping to provide a geographical perspective, supporting the formulation of evidence-based action plans to mitigate their impacts. Our results show that Balochistan, the least developed province of Pakistan, is likely to observe higher levels of IS (95% confidence) during pandemics. Asset ownership, illiteracy, and employment are among the significant factors that drive IS in Pakistan. The geographical evaluation reveals considerable spatial heterogeneity in IS, FI, and several associated factors across the study area. While the higher IS clusters are identified in Khyber Pakhtunkhwa, the hotspots of FI are evident in Sindh province (95% confidence). This study has practical implications for medium- to long-term policy responses to health emergencies, which are essential for building resilience against future pandemics.

Efficacy and Safety of Mesenchymal Stromal Cells for Steroid-Refractory Acute Graft-versus-Host Disease: An Updated Meta-Analysis of Randomized Controlled Trials - Iftikhar Khan; Umama Rehman; Fatima Aslam; Saad Khan; Umna Bhatti; Hussain Ramzan; Fatima Naveed; Javeria Nawaz; Syeda Malaika Raza; Kiran Inam; Faiza Rajput; Syed Muhammad Seyab; et al. (Stem Cell Reviews and Reports, 2025)

Asymmetric Mannich reaction enabled synthesis of alkaloids - Summaya Fatima; Asim Mansha; Samreen Gul Khan; Syed Makhdoom Hussain; Bushra Parveen; Ameer Fawad Zahoor; Aqsa Mushtaq; Rabia Ashraf; Aijaz Rasool Chaudhry; Ahmad Irfan (Molecular Diversity, 2025)

Unlocking the medicinal potential of Ocimum africanum: A review of its phytoconstituents and pharmacological activities - Rohini Yadav; Syed Kaniz Fatima; Sunita Singh Dhawan (South African Journal of Botany, 2025)

Functional trait variability and adaptive strategies of Genus Carex along the elevation gradients - Muhammad Waheed; Fahim Arshad; Muhammad Manzoor; Syed Waseem Gillani; Abeer Al-Andal; Kaniz Fatima (Flora, 2025)

Oxidative phosphorylation and breast cancer progression: insights into PGC-1α’s role in mitochondrial function - Rihab Akasha; Jerlyn Apatan Enrera; Syeda Bushra Fatima; A. M. Hegazy; Weiam Hussein; Muhammad Nawaz; Maali D. Alshammari; Sultan Almuntashiri; Najah Albadari; Mohammed Khaled Bin Break; Rahamat Unissa Syed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

3-Acetyl-11-keto-β-boswellic acid (AKBA) induced antiproliferative effect by suppressing Notch signaling pathway and synergistic interaction with cisplatin against prostate cancer cells - Mahima Verma; Shireen Fatima; Asad Syed; Abdallah M. Elgorban; Islem Abid; Ling Shing Wong; Mohd Sajid Khan; Irfan Ahmad Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Protein sparing by dietary lipids in the diets of Pangasianodon hypophthalmus: an appraisal of growth, body composition, digestive enzymes, and metabolic responses - Sadaf Khadim; Mahroze Fatima; Syed Zakir Hussain Shah; Hamda Azmat; Muhammad Afzal Rashid (Fish Physiology and Biochemistry, 2025)

Green and cost-effective photocatalytic degradation of murexide dye with acid catalyst - Zain Ul Abidin; Adnan Majeed; Muhammad Adnan Iqbal; Muhammad Kashif; Tabinda Fatima; Muhammad Yousif; Muhammad Arbaz; Syed Arslan Hussain; Muhammad Sajid (Clean Technologies and Environmental Policy, 2025)

Correction: Dietary Copper Requirement of Cirrhinus mirigala Juveniles: Effects on Growth Performance, Antioxidant Enzyme Activity and Copper Content in the Whole Body and Tissues - Ayesha Safdar; Syed Zakir Hussain Shah; Mahroze Fatima; Syed Makhdoom Hussain; Noor Khan; Wazir Ali; Razia Iqbal; Kiran Aftab (Biological Trace Element Research, 2025)

Dietary manganese requirement of Cirrhinus mrigala juveniles - Rubina Hayat; Syed Zakir Hussain Shah; Mahroze Fatima; Syed Makhdoom Hussain; Shahzad Ashraf; Wazir Ali (Journal of Trace Elements in Medicine and Biology, 2025)

Dietary zinc requirement of Catla (Catla catla) juveniles - Anam Zafar; Syed Zakir Hussain Shah; Mahroze Fatima; Syed Makhdoom Hussain; Muhammad Mudassar Shahzad; Majid Hussain; Wazir Ali (Aquaculture International, 2025)

Addition of bromelain enzyme to a plant-based diet in Labeo rohita fingerlings: Effects on growth, body composition, enzyme activities, and intestinal morphology - Samra Qudratullah; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Beenish Aftab; Ayesha Khizar; Wazir Ali; Ayesha Tanveer (Aquaculture International, 2025)

Dietary Copper Requirement of Cirrhinus mirigala Juveniles: Effects on Growth Performance, Antioxidant Enzyme Activity and Copper Content in the Whole Body and Tissues - Ayesha Safdar; Syed Zakir Hussain Shah; Mahroze Fatima; Syed Makhdoom Hussain; Noor Khan; Wazir Ali; Razia Iqbal; Kiran Aftab (Biological Trace Element Research, 2025)

Comparative transcriptomic and physiological analysis of extremophilic and non-extremophilic fungi in bioremediation of cadmium (Cd) and strontium (Sr) - Toquier Azam; Xueqi Dai; Xiaoming Chen; Imran Ali; Sen Chen; Fatima Noor; Syed Zeeshan Haider (Environmental Pollution, 2025)

A novel (−)-(2S)-7,4′-dihydroxyflavanone compound for treating age-related diabetes mellitus through immunoinformatics-guided activation of CISD3 - Abdur-Rehman Munir; Saad Ilyas Baig; Muhammad Asif Razzaq; Fatima Rauf; Yasir Ali; Syed Muhammad Abdullah Azam (Biogerontology, 2025)

Valorization of chicken feathers for polyhydroxyalkanoates production using Rohodococcus quinshengii LS18 and the biodegradation studies with the extracted polymer and its blends - Shareen Fatima Rizvi; Syed Khalida Izhar; Aamina Shahab; Akil Ahmad; Mohammed B. Alshammari; Mohd. Rehan Zaheer; Roohi Roohi (Biodegradation, 2025)

Further evidence of biallelic NAV3 variants associated with recessive neurodevelopmental disorder with dysmorphism, developmental delay, intellectual disability, and behavioral abnormalities - Naseebullah Kakar; Selinda Mascarenhas; Asmat Ali; Azmatullah; Syed M. Ijlal Haider; Vaishnavi Ashok Badiger; Mobina Shadman Ghofrani; Nathalie Kruse; Sohana Nadeem Hashmi; Jelena Pozojevic; Saranya Balachandran; Mathias Toft; et al. (Human Genetics, 2025)
Neuron navigators (NAVs) are cytoskeleton-associated proteins well known for their role in axonal guidance, neuronal migration, and neurite growth necessary for neurodevelopment. Neuron navigator 3 (NAV3) is one of the three NAV proteins highly expressed in the embryonic and adult brain. However, the role of the NAV3 gene in human disease is not well-studied. Recently, five bi-allelic and three mono-allelic variants in NAV3 were reported in 12 individuals from eight unrelated families with neurodevelopmental disorder (NDD). Here, we report five patients from three unrelated consanguineous families segregating autosomal recessive NDD. Patients have symptoms of dysmorphism, intellectual disability, developmental delay, and behavioral abnormalities. Exome sequencing (ES) was performed on two affected individuals from one large family, and one affected individual from each of the other two families. ES revealed two homozygous nonsense c.6325C > T; p.(Gln2109Ter) and c.6577C > T; p.(Arg2193Ter) and a homozygous splice site (c.243 + 1G > T) variants in the NAV3 (NM_001024383.2). Analysis of single-cell sequencing datasets from embryonic and young adult human brains revealed that NAV3 is highly expressed in the excitatory neurons, inhibitory neurons, and microglia, consistent with its role in neurodevelopment. In conclusion, in this study, we further validate biallelic protein truncating variants in NAV3 as a cause of NDD, expanding the spectrum of pathogenic variants in this newly discovered NDD gene.

Overview of industrial food fraud and authentication through chromatography technique and its impact on public health - Nabila Aslam; Rida Fatima; Ammar B. Altemimi; Talha Ahmad; Samran Khalid; Syed Ali Hassan; Rana Muhammad Aadil (Food Chemistry, 2024)

Nitrogen and carbohydrate metabolisms are key factors in maize (Zea mays L.) germination under chromium-induced ROS - Muhammad Imran Atta; Syeda Sadaf Zehra; Zhihang Zhuo; Habib Ali; Malik Waseem Abbas; Syed Naveed Abbas; Sadia Sarwar; Fatima Muneer; Irfan Ahmad; Danpping Xu; Hasham S. Almoallim; Mohammad Javed Ansari (Journal of Plant Diseases and Protection, 2024)

RETRACTED ARTICLE: Mitigating potentials of natural herbal supplements against heavy metal toxicity in freshwater fish, Cyprinus carpio - Arzoo Fatima; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K. Sarker; Khalid A. Al-Ghanim; Eman Naeem (Aquaculture International, 2024)

Driving low-carbon mechanisms through smart investments in renewable resources and green finance initiatives among G20 nations - Farzana Fatima Liza; Lili Wei; Syed Tauseef Hassan; Irfan Khan; Fayyaz Ahmad (Journal of Environmental Management, 2024)

Alkaloid-based modulators of the PI3K/Akt/mTOR pathway for cancer therapy: Understandings from pharmacological point of view - Fatima Zohra Mokhfi; Md Al Amin; Mehrukh Zehravi; Sherouk Hussein Sweilam; Uppuluri Varuna Naga Venkata Arjun; Jeetendra Kumar Gupta; Bhaskar Vallamkonda; Anitha Balakrishnan; Manjula Challa; Jyoti Singh; P. Dharani Prasad; Syed Salman Ali; et al. (Chemico-Biological Interactions, 2024)

Deciphering fungicide resistance in Phytophthora: mechanisms, prevalence, and sustainable management approaches - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (World Journal of Microbiology and Biotechnology, 2024)

Effects of Zinc-Gluconate Levels on Growth Performance, Whole-Body Composition, and Mineral and Enzyme Activities of Juvenile Mori (Cirrhinus mrigala) - Zainab Hamid; Syed Zakir Hussain Shah; Mahroze Fatima; Maryam; Hafsa Nadeem; Wazir Ali (Biological Trace Element Research, 2024)

Formulation and Evaluation of Meloxicam Hybrid nano Particles - Mohammed Asif; Kaneez Fatima; Syed Sarim Imam; Sultan Alshehri; Wael A. Mahdi (AAPS PharmSciTech, 2024)

Effects of dietary nano-selenium concentration on growth, proximate chemical composition and antioxidant enzymes, and physiological responses to stressors by juvenile Catla catla - Iqra Sultan; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Hafsa Nadeem; Wazir Ali (Aquaculture, 2024)

Star anise extract supplementation improved growth performance, hepatic-antioxidant enzyme status, hematology, serum biochemistry, and survival against crowding stress in Catla catla - Wazir Ali; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Saima Naveed (Aquaculture, 2024)

Highly selective and effective oxidation of 5-hydroxymethylfurfural by Co-Ni based electrodeposited bimetallic oxide nanostructures - Ghazala Nawaz; Mahnoor Fatima; Zahoor Ahmad; Khurram Saleem Joya; Mohammed Ali Assiri; Syed Imran Abbas Shah; Farhat Yasmeen; Muhammad Naeem Khan (Fuel, 2024)

Physicochemical characterization of microcrystalline cellulose derived from underutilized orange peel waste as a sustainable resource under biorefinery concept - Saima Sohni; Shehla Begum; Rokiah Hashim; Sher Bahadar Khan; Faryal Mazhar; Fatima Syed; Shahid Ali Khan (Bioresource Technology Reports, 2024)

Investigating the impact of coarse aggregate dosage on the mechanical performance of 3D printable concrete - Syed Bustan Fatima Warsi; Dodda Srinivas; Biranchi Panda; Pankaj Biswas (Innovative Infrastructure Solutions, 2024)

Redundant nerve roots indicate higher degree of stenosis in lumbar spine stenotic patients - Karim Rizwan Nathani; Muhammad Danish Barakzai; Hamid Hussain Rai; Komal Naeem; Fatima Mubarak; Haissan Iftikhar; Saad Akhtar Khan; Syed Ather Enam (Acta Neurologica Belgica, 2023)

Exploring and targeting potential druggable antimicrobial resistance targets ArgS, SecY, and MurA in Staphylococcus sciuri with TCM inhibitors through a subtractive genomics strategy - Aafareen Khan; Saman Sohail; Seerat Yaseen; Sareen Fatima; Ayesha Wisal; Sufyan Ahmed; Mahrukh Nasir; Muhammad Irfan; Asad Karim; Zarrin Basharat; Yasmin Khan; Muhammad Aurongzeb; et al. (Functional & Integrative Genomics, 2023)

Quercetin supplementation in the diet of Labeo rohita: Effects on growth, proximate composition, antioxidative indices and immunity - Tahrim Khan; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Maryam; Wazir Ali; Atiqa Sabir; Irum Tahir; Dua Laraib (Animal Feed Science and Technology, 2023)

Low thermal pre-treatment of palm kernel expeller to enhance microalgal hydrogen production - Khairun Nadia Muhamad; Nurul Tasnim Sahrin; Raid Abdulrahman Alakeel; Rabbani Syed; Fatima Musa Ardo; Jia Min Woon; Wen Nee Tan; Chin Kui Cheng; Zakariyya Uba Zango; Chii-Dong Ho; Sze Mun Lam; Jin Chung Sin; et al. (Fuel, 2023)

Phytoremediation potential modulated by structural and functional traits in a saline desert halophyte Fagonia indica Burm. f - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Syed Mohsan Raza Shah; Farooq Ahmad; Majid Anwar; Sana Basharat; Ansa Asghar; Muhammad Ashraf (Environmental Science and Pollution Research, 2023)

Use of dietary β-mannanase supplementation to increase nutrient digestibility and improve growth of juvenile rohu (Labeo rohita) given a feed based on plant ingredients - Rimsha Saleem; Syed Zakir Hussain Shah; Mahroze Fatima; Maryam; Hafsa Nadeem (Aquaculture International, 2023)

Dramatic changes in anatomical traits of a C4 grass Chrysopogon serrulatus Trin. (Poaceae) over a 1000 m elevational gradient - Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Majid Anwar; Mahwish Munir; Muhammad Ashraf; Syed Mohsan Raza Shah; Sana Basharat; Iftikhar Ahmad; Sangam Khalil (Journal of Mountain Science, 2023)

Association of Catechol-O-Methyltransferase Gene Polymorphisms and Haplotypes in the Levodopa-Induced Adverse Events in Subjects with Parkinson’s Disease - Tasneem SD Fatima; Syed Tazeem Fathima; Rukmini Mridula Kandadai; Rupam Borgohain; Boddupally Sreenu; Vijay Kumar Kutala (Indian Journal of Clinical Biochemistry, 2023)

Experimental and numerical study on the structural behaviour of HST, RCC and CFST stub columns under pure axial compression - M. Longshithung Patton; Syed Bustan Fatima Warsi; Dibyendu Adak (Innovative Infrastructure Solutions, 2023)

Factorial analysis for the impact on filtration properties of water-based drilling fluid after the addition of graphene oxide, pure-bore, and sodium alginate - Shaine Mohammadali Lalji; Syed Imran Ali; Muhammad Mohsin Yousufi; Muhammad Arsalan Sultan; Khizra Fatima; Abdur Rahman Misbah (Arabian Journal of Geosciences, 2023)

Evaluating the safety and efficacy of daprodustat for anemia of chronic kidney disease: a meta-analysis of randomized clinical trials - Kaneez Fatima; Warda Ahmed; Asad Saulat Fatimi; Omar Mahmud; Muhammad Umar Mahar; Ayesha Ali; Syed Roohan Aamir; Muhammad Taha Nasim; Muhammad Bilal Islam; Muhammad Talha Maniya; Dua Azim; Shayan Marsia; et al. (European Journal of Clinical Pharmacology, 2022)

Risk of Carcinogenicity Associated with Synthetic Hair Dyeing Formulations: A Biochemical View on Action Mechanisms, Genetic Variation and Prevention - Asif Ali; Moinuddin; Shaziya Allarakha; Shamila Fatima; Syed Amaan Ali; Safia Habib (Indian Journal of Clinical Biochemistry, 2022)

Contribution of structural and functional adaptations of hyper-accumulator Suaeda vera Forssk. ex J.F. Gmel. for adaptability across salinity gradients in hot desert - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Ashraf; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Syed Mohsan Raza Shah; Faakeha Islam; Iftikhar Ahmad; Farial Ejaz; Mehwish Naseer (Environmental Science and Pollution Research, 2022)

Pcal_2031, a RecA/Rad51 homologue from Pyrobaculum calidifontis, complements the ultraviolet light sensitivity of Escherichia coli - Syed Nasim Abbas; Mehwish Aslam; Amina Maqsood; Hafiza Zumra Fatima; Muhammad Arshad Javed; Naeem Rashid (Biologia, 2022)

Development of Optimized Sumatriptan–Prochlorperazine Combined Orodispersible Films Without Disintegrant: in vitro, ex vivo and in vivo Characterization - Sana Javed; Amjad Hussain; Pervaiz Akhtar Shah; Syed Atif Raza; Ubaid Ullah Anwer; Rahat Shamim; Fatima Rasool; Muhammad Ahsan Hafiz; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2022)

Survival strategies in two high altitude Sorghum species from western Himalayas - Khwaja Shafique Ahmad; Anum Javaid; Mansoor Hameed; Sana Fatima; Farooq Ahmad; Muhammad Ashraf; Syed Mohsan Raza Shah; Muhammad Sajid Aqeel Ahmad; Iftikhar Ahmad (Acta Physiologiae Plantarum, 2022)

Phytochemicals from Carissa carandas with potent cytotoxic and anti-inflammatory activities - Zarina Bano; Sabira Begum; Syed Saqib Ali; Zareena Kiran; Bina S. Siddiqui; Ayaz Ahmed; Shariqa Khawaja; Fatima Fatima; Almas Jabeen (Natural Product Research, 2022)

Modulation in Plant Micro-structures Through Soil Physicochemical Properties Determines Survival of Salsola imbricata Forssk. in Hypersaline Environments - Nargis Naz; Sana Fatima; Mansoor Hameed; Farooq Ahmad; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Hina Shahid; Ummar Iqbal; Muhammad Kaleem; Syed Mohsan Raza Shah; Iftikhar Ahmad (Journal of Soil Science and Plant Nutrition, 2022)

Geospatial assessment of water quality using principal components analysis (PCA) and water quality index (WQI) in Basho Valley, Gilgit Baltistan (Northern Areas of Pakistan) - Syeda Urooj Fatima; Moazzam Ali Khan; Farhan Siddiqui; Nadeem Mahmood; Nasir Salman; Aamir Alamgir; Syed Shahid Shaukat (Environmental Monitoring and Assessment, 2022)

Moderating role of institutional quality in validation of pollution haven hypothesis in BRICS: a new evidence by using DCCE approach - Imran Sharif Chaudhry; Weihua Yin; Syed Ahtsham Ali; Muhammad Faheem; Qaiser Abbas; Fatima Farooq; Saeed Ur Rahman (Environmental Science and Pollution Research, 2022)

In Silico Mutagenesis-Based Remodelling of SARS-CoV-1 Peptide (ATLQAIAS) to Inhibit SARS-CoV-2: Structural-Dynamics and Free Energy Calculations - Abbas Khan; Shaheena Umbreen; Asma Hameed; Rida Fatima; Ujala Zahoor; Zainib Babar; Muhammad Waseem; Zahid Hussain; Muhammad Rizwan; Nasib Zaman; Shahid Ali; Muhammad Suleman; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Analysis of Intrinsic and Extrinsic Coagulation Pathway Factors in OCP Treated PCOS Women - Saika Manzoor; Mohd A. Ganie; Sabhiya Majid; Iram Shabir; Iram A. Kawa; Qudsia Fatima; Humira Jeelani; Syed Douhath Yousuf; Fouzia Rashid (Indian Journal of Clinical Biochemistry, 2021)

Correction to: A study of thermal controls in rapidly developing city using remotely sensed satellite data: spatiotemporal perspective - Khalid Mahmood; Syed Ahmed Raza; Syeda Yuman Fatima (Acta Geophysica, 2021)

Survival Strategies in Khavi Grass [Cymbopogon jwarancusa (Jones) Schult.] Colonizing Hot Hypersaline and Arid Environments - Sana Fatima; Mansoor Hameed; Nargis Naz; Syed Mohsan Raza Shah; Mehwish Naseer; Muhammad Sajid Aqeel Ahmad; Muheammad Ashraf; Farooq Ahmad; Sangam Khalil; Iftikhar Ahmad (Water, Air, & Soil Pollution, 2021)

A study of thermal controls in rapidly developing city using remotely sensed satellite data: spatiotemporal perspective - Khalid Mahmood; Syed Ahmed Raza; Syeda Yuman Fatima (Acta Geophysica, 2021)

Infectious Waste Management Strategy during COVID-19 Pandemic in Africa: an Integrated Decision-Making Framework for Selecting Sustainable Technologies - Amine Belhadi; Sachin S. Kamble; Syed Abdul Rehman Khan; Fatima Ezahra Touriki; Dileep Kumar M. (Environmental Management, 2020)

Spatial modeling of Dengue prevalence and kriging prediction of Dengue outbreak in Khyber Pakhtunkhwa (Pakistan) using presence only data - Hammad Ahmad; Asad Ali; Syeda Hira Fatima; Farrah Zaidi; Muhammad Khisroon; Syed Basit Rasheed; Ihsan Ullah; Saleem Ullah; Muhammad Shakir (Stochastic Environmental Research and Risk Assessment, 2020)

Association analysis and allelic distribution of deletion in CC chemokine receptor 5 gene (CCR5Δ32) among breast cancer patients of Pakistan - Faria Fatima; Saima Saleem; Abdul Hameed; Ghulam Haider; Syed Aqib Ali Zaidi; Madiha Kanwal; Sitwat Zehra; Abid Azhar (Molecular Biology Reports, 2019)

Phytochemical composition, biological potential and enzyme inhibition activity of Scandix pecten-veneris L. - Abdul Wahab; Syed Aleem Jan; Abdur Rauf; Zia ur Rehman; Zahid Khan; Aftab Ahmed; Fatima Syed; Sher Zaman Safi; Hamayun Khan; Muhammad Imran (Journal of Zhejiang University-SCIENCE B, 2018)

Chaetomium endophytes: a repository of pharmacologically active metabolites - Nighat Fatima; Syed Aun Muhammad; Ibrar Khan; Muneer Ahmed Qazi; Irum Shahzadi; Amara Mumtaz; Muhammad Ali Hashmi; Abida Kalsoom Khan; Tariq Ismail (Acta Physiologiae Plantarum, 2016)

Interaction of Copper with Iron, Iodine, and Thyroid Hormone Status in Goitrous Patients - Tasneem Gul Kazi; Ghulam Abbas Kandhro; Hassan Imran Afridi; Naveed Kazi; Jameel Ahmed Baig; Mohammad Balal Arain; Abdul Qadir Shah; Nasreen Syed; Sham Kumar; Nida Fatima Kolachi; Sumaira Khan (Biological Trace Element Research, 2010)

Erratum to: The effect of implantation on scaffoldless three-dimensional engineered bone constructs - Michael J. Smietana; Fatima N. Syed-Picard; Jinjin Ma; Tatiana Kostrominova; Ellen M. Arruda; Lisa M. Larkin (In Vitro Cellular & Developmental Biology - Animal, 2010)

The effect of implantation on scaffoldless three-dimensional engineered bone constructs - Michael J. Smietana; Fatima N. Syed-Picard; Jinjin Ma; Tatiana Kostrominova; Ellen M. Arruda; Lisa M. Larkin (In Vitro Cellular & Developmental Biology - Animal, 2009)

Development of a new orthotopic animal model of metastatic liver cancer in the rabbit VX2 model: effect on metastases after partial hepatectomy, intra-arterial treatment with 3-bromopyruvate and chemoembolization - Josephina A. Vossen; Manon Buijs; Labiq Syed; Fatima Kutiyanwala; Mustafa Kutiyanwala; Jean-Francois H. Geschwind; Mustafa Vali (Clinical & Experimental Metastasis, 2008)

One-Year pollen and spore calendars of Saudi Arabia Al-Khobar, Abha and Hofuf - Syed M. Hasnain; Khatija Fatima; Abdulrahman Al-Frayh; Sultan T. Al-Sedairy (Aerobiologia, 2005)

Prevalence of airborne basidiospores in three coastal cities of Saudi Arabia - Syed M. Hasnain; Khatija Fatima; Abdulrahman Al-Frayh; Sultan T. Al-Sedairy (Aerobiologia, 2005)

Cladosporium and respiratory allergy: Diagnostic implications in Saudi Arabia - Syed M. Hasnain; Abdulrahman S. Al-Frayh; Abdulrahman Al-Suwaine; Mohammad O. Gad-El-Rab; Khatija Fatima; Sultan Al-Sedairy (Mycopathologia, 2004)